2020
DOI: 10.1029/2020gc008953
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity of the Incoming Plate and Forearc Near the Mariana Trench Recorded by Ocean Bottom Seismographs

Abstract: Earthquakes near oceanic trenches are important for studying incoming plate bending and updip thrust zone seismogenesis, yet are poorly constrained using seismographs on land. We use an ocean bottom seismograph (OBS) deployment spanning both the incoming Pacific Plate and the forearc to study seismicity near the Mariana Trench. The yearlong deployment in 2012-2013 consisted of 20 broadband OBSs and 5 suspended hydrophones, with an additional 59 short period OBSs and hydrophones recording for 1 month. We locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 125 publications
(205 reference statements)
1
10
1
Order By: Relevance
“…For example, previous studies suggested the neutral plane with a global average depth of 30-40 km marks the bottom boundary of the mantle hydration, assuming that pore water cannot penetrate the compressional stress regime (Chapple & Forsyth, 1979). Based on near-field OBS observations, the extensional earthquakes are estimated at the depth of ∼20 km below the Moho in the central Mariana, which is much deeper than previous results (Emry et al, 2014) and consistent with the estimated hydration extent derived from the SV-wave velocities (Eimer et al, 2020).…”
Section: Coherence Between Low-velocity Zone (Hydration Zone) and Ben...supporting
confidence: 86%
“…For example, previous studies suggested the neutral plane with a global average depth of 30-40 km marks the bottom boundary of the mantle hydration, assuming that pore water cannot penetrate the compressional stress regime (Chapple & Forsyth, 1979). Based on near-field OBS observations, the extensional earthquakes are estimated at the depth of ∼20 km below the Moho in the central Mariana, which is much deeper than previous results (Emry et al, 2014) and consistent with the estimated hydration extent derived from the SV-wave velocities (Eimer et al, 2020).…”
Section: Coherence Between Low-velocity Zone (Hydration Zone) and Ben...supporting
confidence: 86%
“…The refraction data sample only a few km beneath the Moho, and cannot provide information on how deep bend-related faulting and hydration extend. However, other observations, including Rayleigh wave dispersion and anisotropy (Cai et al, 2018) and earthquake hypocenters (Eimer et al, 2020;Emry et al, 2014), show that extensional faulting extends to greater depths than sampled in this study.…”
Section: Implications For Subduction Zone Water Fluxcontrasting
confidence: 48%
“… 37 , 38 A well-known example of the hydration of the incoming lithosphere comes from the Middle America Trench, where active bending-related faulting across the entire ocean trench slope penetrates at least 20 km into the plate, promoting the deep percolation of water and hydration of the crust and upper mantle. 22 , 39 , 40 The hydration of upper mantle rock has also been documented below the Moho of the subducting slab at the northern central Chile, 41 central Chile, 23 southernmost Mariana, 42 and Mariana 43 trenches, as shown by a notable reduction in compressional mantle velocities, with a penetration depth of 1–2 km, 22 and even 5–7 km, into the mantle. 41 , 44 , 45
Figure 3 Bending-related normal faults and fracture zones in the southern Mariana Trench (A) Topographic map showing abundant bending-related normal faults occurring on the incoming plate of the southern Mariana Trench.
…”
Section: Hadal Lithosphere Associated Fluids and Life Activitiesmentioning
confidence: 93%
“…59 The work by Du et al 59 provides direct evidence that the structural deformation of the incoming plate could substantially influence the hydration of upper basaltic crust, which fosters chemical exchange between the upper ocean crust and seawater in a new way. 43 These newly discovered fluid discharge fields are exhibited by small-scale mud volcanoes and pockmarks in association with varied altered mafic rocks that crop out on the trench slope and are mainly composed of iddingsite. 59 Chemically and physically, this phenomenon differs from the serpentine mud volcano formation associated with the shallower Mariana forearc region.…”
Section: Hydration Of Basaltic Lithosphere Supporting Fluid Dischargementioning
confidence: 99%